Recurrence of atrial fibrillation and late cardiovascular events in patients with persistent atrial fibrillation after restoration of sinus rhythm - U.P. Chernyaha-Royko; N.S. Pavlyk; M.S. Sorokivskyy; A.V. Aker; O.J. Zharinov (Кардіохірургія та інтервенційна кардіологія)
The aim – to study the role of late recurrences of AF in predicting adverse course of the disease in patients with persistent AF after cardioversion at 9-month follow-up.